RASIO KEUANGAN DAN UKURAN PERUSAHAAN SEBAGAI PREDIKTOR AGRESIVITAS PAJAK (Studi Pada Perusahaan Manufaktur Subsektor Barang Konsumsi Di BEI) - Rr. Tjahjaning Poerwati; Ida Nurhayati; Achmad Badjuri; Sri Sudarsi (Faculty of Economic and Business Universitas STIKUBANK, 2021)
This study aimed to examine the tax aggressiveness through the components of financial ratios namely liquidity, leverage, profitability, and corporate size in manufacturing companies of consumer goods sub-impurities on the Indonesia Stock Exchange for the period 2015-2018. The selection of samples uses proposive sampling with the criteria of consumer goods subsector companies that report complete finances and companies earn profits. Based on these criteria, a sample of 98 observations was obtained. Analytical techniques use multiple linear regression analysis. The results showed that liquidity negatively affects tax aggressiveness, leverage negatively affects tax aggressiveness, profitability positively affects tax aggressiveness, and corporate size negatively affects tax aggressiveness. Keywords: Tax Aggressiveness, Liquidity, Leverage, Profitability, Size of Fir